(untitled) (Revista de Estudios Europeos, 2026)
The purpose of this article is to discuss the recent history of Albania within the framework of its accession process to the European Union. We will take an approach to the adaptation of this country to liberal democracy and the market economy since the collapse of the so-called real socialism, which adopted unique characteristics in Albania, until the present moment, placing special emphasis on the relationship of the Balkan nation with the community institutions.